A 2-equation model of the North Atlantic economies, a dynamic panel study - David Kiefer (The University of Utah, Department of Economics, 2010)
Carlin and Soskice (2005) advocate a 3-equation model of stabilization policy to replace the conventional IS-LM-AS model. One of their new equations is a monetary reaction rule MR derived by assuming that governments have performance objectives, but are constrained by an augmented Phillips curve PC. They label their replacement model the IS-PC-MR. Central banks achieve the PC-MR solution by setting interest rates along an IS curve. Observing that governments have more tools than just the interest rate, we simplify their model to 2 equations. We develop a state space econometric specification as the solution of these equations, adding a random walk model of the unobserved potential growth. Applying this method to a panel of North Atlantic countries, we find it historically consistent with a few qualifications. For one, governments are more likely to target growth rates, than output gaps. And, inflation expectations are more likely backward looking, than rational, but a two-step estimation based on a forward-looking sticky-price model dramatically improves the empirical fit. Significant interdependence can be seen in the between-country covariance of inflation and growth shocks.
Keywords: E61; E63; 330; New Keynesian; Kalman filtering; open economies